IJMSIR 2022
DOI: 10.53075/ijmsirq/6867556758
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nutritional Knowledge and Dietary Compliance among Type 2 Diabetes Mellitus Patients at the Bono Regional Hospital, Sunyani, Ghana

Abstract: The study assessed nutritional knowledge and dietary compliance of type 2 diabetes mellitus (T2DM) patients in the context of diabetes self-care, and the association between nutritional knowledge and dietary compliance. A report from a recent population-based study indicates that between 3.3% and 6% of Ghanaian adults are living with diabetes mellitus (DM) and this is projected to reach 820,000 by 2035. Diet therapy and self-care form an integral part of T2DM management, however, little is known about the nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…This will enable T2DM patients to choose their foods properly, reduce certain foods or even avoid them completely to manage their blood sugar levels properly [24]. The results of this study are in accordance with the results of research conducted by Setyaningrum et al ( 2019) and Nketia and Adobasom-Anane (2022) [25,26]. With good knowledge or understanding related to nutrition for diabetes mellitus patients, patients better understand the urgency and consequences of implementing a diet so that patients will tend to stick to their diet compared to patients who have low nutritional knowledge.…”
Section: Resultssupporting
confidence: 89%
“…This will enable T2DM patients to choose their foods properly, reduce certain foods or even avoid them completely to manage their blood sugar levels properly [24]. The results of this study are in accordance with the results of research conducted by Setyaningrum et al ( 2019) and Nketia and Adobasom-Anane (2022) [25,26]. With good knowledge or understanding related to nutrition for diabetes mellitus patients, patients better understand the urgency and consequences of implementing a diet so that patients will tend to stick to their diet compared to patients who have low nutritional knowledge.…”
Section: Resultssupporting
confidence: 89%
“…Several studies have shown that the possession of adequate dietary knowledge significantly influences effective dietary practices. Research conducted by Jemal et al [ 45 ] indicated that higher knowledge significantly resulted in improved dietary practice, supporting a similar finding in Ghana [ 46 ] which demonstrated a significant association between good nutritional knowledge and dietary adherence. Additionally, Adam et al [ 34 ] conducted a cross-sectional study in Sudan among patients with T2D to assess dietary knowledge, attitude and practices.…”
Section: Discussionsupporting
confidence: 58%
“…The largest secondary-level hospital (by patient attendance and specialist care) in the Sunyani Municipality and the Bono Region is the Bono Regional Hospital. The hospital serves as the major referral center for both primary-level healthcare facilities and secondary-level hospitals in the Bono, Bono East, and Ahafo Regions of Ghana (Nketia et al, 2022). The mental health unit of the Bono Regional Hospital provides 24-hour healthcare, including expert services for patients who have health insurance and those who do not.…”
Section: Study Design and Study Areamentioning
confidence: 99%